Efficacy and safety of apremilast, an oral phosphodiesterase 4 inhibitor, in patients with moderate‐to‐severe plaque psoriasis over 52 weeks: a phase III, randomized controlled trial (ESTEEM 2). (7th November 2015) - Paul, C.; Cather, J.; Gooderham, M.; Poulin, Y.; Mrowietz, U.; Ferrandiz, C.; Crowley, J.; Hu, C.; Stevens, R.M.; Shah, K.; Day, R.M.; Girolomoni, G.; et al.
Summary: Background: Apremilast, an oral phosphodiesterase 4 inhibitor, regulates immune responses associated with psoriasis. Objectives: ESTEEM 2 evaluated the efficacy and safety of apremilast 30 mg twice daily for moderate‐to‐severe plaque psoriasis. Methods: This phase III, double‐blind, placebo‐controlled trial randomized adults to apremilast or placebo (2 : 1). At week 16, placebo patients switched to apremilast. At week 32, apremilast patients achieving ≥ 50% reduction in Psoriasis Area and Severity Index (PASI 50) were rerandomized (1 : 1) to continue apremilast or receive placebo. Upon loss of 50% of PASI improvement obtained at week 32, patients rerandomized to placebo resumed apremilast. Results: The modified intention‐to‐treat population (full analysis set) included 137 placebo and 274 apremilast patients. At week 16, significantly more apremilast patients achieved PASI 75 (28·8%), PASI 50 (55·5%) and static Physician's Global Assessment score of 0 or 1 (20·4%) vs. placebo (5·8%, 19·7%, 4·4%, respectively; P  <   0·001). Most patients rerandomized to apremilast at week 32 had a PASI 50 response at week 52 (80%). Patients treated with apremilast showed significant improvements in quality of life (as assessed by the Dermatology Life Quality Index) and pruritus at week 16 compared with placebo ( P  <   0·001). The exposure‐adjusted incidence of adverse events did not increase with continued apremilast treatment for up to 52 weeks. The most common adverse events were nausea, diarrhoea, nasopharyngitis and upper respiratory tract infection. Conclusions: Apremilast was effective in the treatment of moderate‐to‐severe plaque psoriasis over 52 weeks. Abstract : What's already known about this topic? Psoriasis is a chronic inflammatory disease of the skin resulting from an uncontrolled immune response, which leads to a chronic imbalance in the production of pro‐ and anti‐inflammatory cytokines. Recent surveys show that many patients with psoriasis report discontinuing treatment with conventional systemic agents or biologics due to lack of tolerability, safety issues, lack or loss of effectiveness, burden of monitoring or injections. What does this study add? In ESTEEM 2, apremilast, an oral phosphodiesterase 4 inhibitor, significantly reduced the severity of moderate‐to‐severe plaque psoriasis over 16 weeks, with response generally maintained in patients continuing apremilast for 52 weeks. Apremilast was effective in difficult‐to‐treat nail, scalp and palmoplantar psoriasis and in improving pruritus and skin discomfort/pain. Apremilast demonstrated an acceptable safety profile; no new significant adverse events emerged with continued apremilast exposure for up to 52 weeks. Linked Comment: Gniadecki, Br J Dermatol 2015; 173: 1355–56 .